Bulgaria : Second Review Under the Stand-By Arrangement and Requests for Waiver of Performance Criteria and for Postponement of Third Review. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Second Review Under the Stand-By Arrangement and Requests for Waiver of Performance Criteria highlights Bulgaria's economic growth, fiscal policy, and reforms. The economic program for 2006 relies on fiscal and credit restraint to rein in demand and strengthen the balance sheets of government and banks, and on structural reforms to stimulate supply. Quarterly credit growth limits and higher penalties for exceeding them are expected to help ensure achievement of this target. Measures to slow down household credit should additionally contribute to current account adjustment.